Analisis Strategi Pemasaran Dengan Media Sosial Marketing Pada Penjualan Properti di Brighton Real Estate - Susanto, Dodik; Izazi, Zsa Zsa (PUTRA JAWA PUBLISHER, 2024)
This research analyzes marketing strategies using social media in property sales by Brighton Real Estate. In this digital era, social media has become a powerful platform for promoting products and services. This research aims to explore the effectiveness of social media marketing strategies in increasing property sales. The research method used is a case study, with data collected through interviews with property agents, social media content analysis, and consumer surveys. The research results show that the use of social media in Brighton Real Estate's property marketing strategy has had a positive impact on sales. Social media allows real estate agents to reach a wider audience, increase engagement and build relationships with potential buyers. However, this research also identified several challenges faced in implementing social media marketing strategies, such as the difficulty of measuring ROI (Return on Investment) appropriately and changes in social media platform algorithms that can affect content reach. In conclusion, marketing strategies using social media have opened up new opportunities for Brighton Real Estate to increase its property sales. By utilizing social media effectively, companies can expand their market reach and increase interactions with potential buyers. This research provides valuable insight for other real estate companies looking to leverage the potential of social media marketing in their industry.